Understanding the role of organizational factors in shaping the research careers of women academics in higher education - Georgeta Ion (Springer, 2014)
This paper represents an attempt to make a theoretical contribution to its knowledge base through an analysis of the group factors which contribute to the success of women academics engaged in research within the area of social sciences. The data were obtained through a series of in-depth interviews carried out at public universities in Catalonia, with women academics -all of whom were the heads of research groups recognized by the Generalitat [Regional Government] of Catalonia. The findings indicate that research groups provide a supportive and effective environment for female researchers enabling them to develop their academic careers, as measured by such key performance indicators as the number of publications and successful applications for research funding.